Pesantren and Ecotheology: Mainstreaming Ecological Consciousness in Pesantren Langitan, East Java, Indonesia - Yardlo, Moh; Muktafi, Muktafi; Mahzumi, Fikri; Arifka, Angga; Sudarman, Mei Ariani (Academia Publication, 2024)
This participatory research aimed to enhance the ecological consciousness of the Santri (students) of Pesantren Langitan, a traditional Islamic boarding school in Tuban, East Java, Indonesia. This pesantren was chosen as the subject based on its geographical location along the Solo River. From an ecological perspective, this location has facilitated the implementation of various environmental initiatives, including promoting green consciousness among the local community, encouraging reforestation along the riverbanks, discouraging waste disposal into the river, and other similar actions aimed at preserving the river ecosystem. Another factor that contributed to the selection of Pesantren Langitan as the subject was its traditional Islamic boarding school nature, focusing on studying classical Islamic texts (kitab kuning). Therefore, the research will likely contribute to promoting Islamic ecotheology. The research employed a participatory action approach, wherein Kyai, Ustaz, and santri were actively engaged in the program's planning, implementation, and evaluation. The theme-based program yielded successful outcomes in four key areas: (1) enhancing green consciousness among the santri, (2) formulating a green fiqh concept, (3) promoting green da'wa on social media, and (4) implementing green activities within the pesantren environment.